2022
DOI: 10.3390/molecules27051526
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Human Serum Albumin and Sulfadimethoxine Determined Using Spectroscopy and Molecular Docking

Abstract: Sulfonamides are widely used antibiotics in agricultural production. However, the potential threat of these drugs to human health has increased global concern. Human serum albumin (HSA) is the main reservoir and transporter of exogenous small molecules in humans. In this study, the interaction between sulfadimethoxine (SMT) and human serum albumin (HSA) was studied using spectroscopy and computer simulation. Our results showed that the hydrogen bonding and van der Waals forces drove SMT to enter the binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…The negative values of both ▵H o and ▵S o confirm the involvement of hydrogen bonds and van der Waals forces in the HSA‐zinc(II) complex binding process [37] . These findings are consistent with the results reported in the literature for HSA binding to sulfadimethoxine, [34d] dicofol, [34a] and BSA binding to ZnSe QDs, [34b] also, HSA / BSA interaction with the complexes of zinc and iron [34c] . As well, HSA interaction with [Zn(bpy)(Gly)]NO 3/ [Zn(phen)(Gly)]NO 3 [38] and zinc(II) complexes synthesized from two types of Schiff base [6b,39] …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The negative values of both ▵H o and ▵S o confirm the involvement of hydrogen bonds and van der Waals forces in the HSA‐zinc(II) complex binding process [37] . These findings are consistent with the results reported in the literature for HSA binding to sulfadimethoxine, [34d] dicofol, [34a] and BSA binding to ZnSe QDs, [34b] also, HSA / BSA interaction with the complexes of zinc and iron [34c] . As well, HSA interaction with [Zn(bpy)(Gly)]NO 3/ [Zn(phen)(Gly)]NO 3 [38] and zinc(II) complexes synthesized from two types of Schiff base [6b,39] …”
Section: Resultssupporting
confidence: 91%
“…The types of non‐covalent interactions including hydrogen bonds, van der Waals forces, hydrophobic, and electrostatic interactions have a fundamental contribution in ligand‐protein binding [36] . The thermodynamic analysis is a classical approach evaluating these interactions according to the theory proposed by Ross [34d] . The forces mentioned above are indicated by the symbol and quantity of varied thermodynamic constants, such as ΔH o (enthalpy change), ΔS o (entropy change), and ΔG o (Gibbs free energy change) [36] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steady-state fluorescence spectroscopy, a simple and convenient method, can judge the occurrence of ligand-protein interactions and further provide vital information, such as quenching mechanism, binding constant, number of binding sites, and thermodynamic data [9,10]. The effect of GDC-0941 on the fluorescence intensity of HSA at 298 K is shown in Figure 5A.…”
Section: Quenching Mechanism Studiesmentioning
confidence: 99%
“…Human serum albumin (HSA) is a principal extracellular protein with a concentration of 40 mg•mL −1 or 0.6 mM in blood plasma and contains 50-60% of total plasma protein in humans [7,8]. Research showed that the distribution, free concentration, and metabolism of drugs can be considerably altered as a result of their binding to HSA [9][10][11]. If the affinity of the drug binding to HSA in the plasma is strong, the drug will be transported to the target tissue and cannot be dissociated from HSA.…”
Section: Introductionmentioning
confidence: 99%